Shackling the footloose firm? Factor interests and majority voting - Carl-Johan Belfrage; Fredrik Gallo (Lund University, School of Economics and Management, Department of Economics, 2006)
Adding majority voting to a simple new economic geography model, we analyse under which circumstances politically determined barriers to international firm relocation exist. Two countries, differing in market size, consider abolishing restrictions on firm mobility. Eliminating these restrictions will fully or partially de-industrialize the small country as firms relocate to the larger market. We show that there is unanimous support for (resistance against) the removal of obstacles to firm relocation in the large (small) country if the country size difference is small, while a large difference in size gives rise to domestic conflicts of interest and international cross-factor alignments of interests. Furthermore, trade liberalisation may have facilitated the removal of barriers to firm relocation in large countries. Finally, political integration between trading countries is likely to contribute to the removal of barriers to firm relocation, and support for (resistance against) such a development comes primarily from the immobile factor in the large (small) country.
Keywords: F12; F13; F15; 330; barriers to firm relocation; new economic geography; majority voting; public policy